Machine-to-Machine (M2M) in ubiquitous computing - Lam, Tiago Miguel Gameiro (2014)
Although the area of Machine-to-Machine communications and, consequently, the Internet of Things, have undergone a great improvement regarding interoperability, there is still no ’de facto’ solution proposal to achieve large scale, even global, interoperability. As a first step, this work provides a theoretical analysis of proposals relevant to the area, mainly analysing how they achieve some essential requirements for the Internet of Things, such as scalability, heterogeneity and management. Later, focusing in ETSI’s M2M standard, is first given a high-level description of its vision, approach and architecture, and then, finally, from a more practical point of view, is also presented and tested a functional implementation of an ETSI M2M compliant gateway, which provides an empirical evaluation of the standard.